Globus Pallidus Internus Deep Brain Stimulation for Disabling Diabetic Hemiballism/Hemichorea - Byung-chul Son; Jin-gyu Choi; Hak-cheol Ko (Case Reports in Neurological Medicine)
Unilateral hemichorea/hemiballism (HH) associated with contralateral neuroimaging abnormalities of the basal ganglia, which is characterized by T1 hyperintensity on magnetic resonance imaging (MRI) and is secondary to diabetic nonketotic hyperglycemia, is a rare and unique complication of poorly controlled diabetes mellitus (DM). Although almost all prior reports have documented rapid resolution of HH within days after normalization of blood glucose levels, medically refractory persistent HH has been noted. The experience of surgical intervention for persistent HH is limited. A 46-year-old, right-handed female patient with type 2 DM presented with refractory diabetic HH on the left side of 6 months’ duration despite DM control and neuroleptic medication usage. Image-guided deep brain stimulation (DBS) on the right globus pallidus internus (GPi) was performed. A mechanical micropallidotomy effect was observed and chronic stimulation of GPi was quite effective in symptomatic control of diabetic HH until a 16-month follow-up visit. DBS of the GPi can be an effective treatment for medically refractory diabetic HH.